Measurement of scintillation and ionization yield with high-pressure gaseous mixtures of Xe and TMA for improved neutrinoless double beta decay and dark matter searches. (October 2015) - Nakajima, Y; Goldschmidt, A; Matis, H S; Nygren, D; Oliveira, C; Renner, J
Abstract: Liquid Xe TPCs are among the most popular choices for double beta decay and WIMP dark matter searches. Gaseous Xe has intrinsic advantages when compared to Liquid Xe, specifically, tracking capability and better energy resolution for double beta decay searches. The performance of gaseous Xe can be further improved by molecular additives such as trimethylamine(TMA), which are expected to (1) cool down the ionization electrons, (2) convert Xe excitation energy to TMA ionizations through Penning transfer, and (3) produce scintillation and electroluminescence light in a more easily detectable wavelength (300 nm). These features may provide better tracking and energy resolution for double-beta decay searches. They are also expected to enhance columnar recombination for nuclear recoils, which can be used for searches for WIMP dark matter with directional sensitivity. We constructed a test ionization chamber and successfully measured scintillation and ionization yields at high precision with various Xe and TMA mixtures and pressures. We observed the Penning effect and an increase in recombination with the addition of TMA. However, many undesired features for dark matter searches, such as strong suppression of the scintillation light and no sign of recombination light, were also found. This work has been carried out within the context of the NEXT collaboration.